Hybrid potentiodynamic/potentiostatic electrodeposition of thin and compact tin dioxide on indium tin oxide electrodes. (1st March 2023) - Ramírez, Daniel; Riveros, Gonzalo; Díaz, Patricia; Faúndez, Martín; Verdugo, Javier; Verdugo, Marcelo; Martin, Francisco; López-Escalante, María Cruz; Gau, Daniel L.; Dalchiele, Enrique A.; Marotti, Ricardo E.
Abstract: Electrodeposition of conformal and compact SnO2 films on transparent conductive oxides (TCOs) has been hardly achieved thus limiting its application in fully solid solar cells such as those based in perovskite absorbers. Here are presented high-quality n-type semiconducting tin (VI) oxide (SnO2 ) thin films, successfully grown using a hybrid potentiodynamic/potentiostatic approach on both ITO and FTO coated glass substrates after a detailed optimization that included both annealing steps between eletrodepositions. A solution chemistry study together with a spectrophotometric analysis was useful to determine the one-hour time window of stability for the chosen electrolyte as source of tin. Formation mechanisms based in thermodynamic data and accumulated mass measurements using an electrochemical quartz crystal microbalance (EQCM) are discussed. From the EQCM study the growth rate of films was also estimated in good agreement with high resolution transmission electron microscopy (HR-TEM) analysis. Field emission scanning electron microscopy (FE-SEM) images and X-ray diffraction (XRD) data revealed that substrates are well-covered, crystalline, conformal and free of defects ( e.g . without pinholes). The absence of these defects was also well supported by cyclic voltammetry measurements using the ferricyanide/ferrocyanide redox couple. XPS also confirmed the presence of Sn 4+ in optimized films. From the optical properties, after carefully eliminating the influence of oscillations due to interference, a direct bandgap energy at 3.60 eV can be deduced. Another indirect bandgap energy at 3.30 eV can also be possible. The hybrid potentiodynamic/potentiostatic protocol to prepare SnO2 paves a way to prepare compact, transparent and well covering films suitable as electron transporting layer (ETL) for applications in both photoelectrochemical and solid-state solar cells.